Adaptation, underground. (1st June 2013) - Watts, Peter
I review the thematically-linked articles presented in the current issue, from the perspective of a naïve outsider with dual citizenship in the disciplines of fiction and biology. The parallels Nic Clear ('Refreshingly Unconcerned With The Vulgar Exigencies of Veracity and Value Judgement: The Utopian Visions of Iain M Banks' The Culture and Constant's New Babylon') draws between the scenarios of Iain Banks' 'Culture' and Nieuwenhuys's 'New Babylon' may highlight cognitive estrangement as a prerequisite (or perhaps, an inevitable side-effect) of Utopia. Nandita Mellamphy compares the biological ecology central to Frank Herbert's Dune books with Laruelle's 'generic ecology' in 'Terra-&-Terror Ecology: Secrets from the Arrakeen Underground'; while I have misgivings about the misappropriation of biological terminology, I do not dispute the central assertion that the only path to success in an ecological context may be through surrender. Felix Robbins' evolving architectural constructs ('Unstable grounds: investigating ulterior spaces for practicing') strongly echo – perhaps inadvertently – the 'biomorphs' created by Richard Dawkins to illustrate evolutionary principles. Ben Woodward's 'The new curses of tomb space' – a rumination on subterranean aspects of both scientific exploration and the environmental consequences of nuclear technology along deep timescales – is, of all the papers presented, perhaps the most literally tied to the issue's theme of 'Chthonic Deluge'. However, all four works may be more tightly bound by evolutionary metaphors than by subterranean ones.